2022
DOI: 10.1039/d2ma00683a
|View full text |Cite
|
Sign up to set email alerts
|

Morphological evolution driven semiconducting nanostructures for emerging solar, biological and nanogenerator applications

Abstract: Metal oxide nanostructures are most fascinating smart and functional materials owing to their outstanding wide and tuneable band gap, biocompatibility, high electrochemical coupling coefficient, high photostability, high-sensitivity, non-toxicity, high electron...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 299 publications
(460 reference statements)
0
8
0
Order By: Relevance
“…Aside from lead-rich piezoelectric materials, such as barium titanate, lithium niobate, barium zirconate titanate–barium calcium titanate-, and bismuth sodium titanate-based materials have no obvious toxic effects . Nontoxic zinc oxide (ZnO) and aluminum nitride (AlN) and Gallium nitride (GaN) are still attractive biomedical materials. On the other hand, organic piezoelectric materials, such as polyvinylidene fluoride (PVDF), , and poly­( l -lactic acid) (PLLA), also have no related toxicity reports.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from lead-rich piezoelectric materials, such as barium titanate, lithium niobate, barium zirconate titanate–barium calcium titanate-, and bismuth sodium titanate-based materials have no obvious toxic effects . Nontoxic zinc oxide (ZnO) and aluminum nitride (AlN) and Gallium nitride (GaN) are still attractive biomedical materials. On the other hand, organic piezoelectric materials, such as polyvinylidene fluoride (PVDF), , and poly­( l -lactic acid) (PLLA), also have no related toxicity reports.…”
Section: Discussionmentioning
confidence: 99%
“…These natural phytochemicals participate in redox reactions which involve electron exchange between metal precursors and phytochemicals and also prevent the agglomeration of NPs. , To synthesize NPs from metal salts using green approaches, hazardous chemical substances are not used, making it a sustainable alternative to conventional methods. Plant-mediated NP synthesis has a number of benefits over microbe-mediated synthesis in which complicated procedures are required for keeping microbiological colonies alive . Plant-mediated synthesis allows large scale manufacturing; however, several issues related to the quality of the NPs and controlled morphology and size remain key bottlenecks. ,, …”
Section: Green Synthesis Of Metal/metal Oxide Nanoparticlesmentioning
confidence: 99%
“… Recently, NPs have emerged as new tools that can be used to combat deadly bacterial infections. Distinct physicochemical traits of NPs make them promising candidates to achieve enhanced therapeutic efficacy against resilient MDR bacterial infections and even bacterial biofilms. , Recently, Slavin et al showed the effectiveness of Ag NPs against both Gram-positive and Gram-negative MDR bacteria including Staphylococcus aureus , Staphylococcus epidermidis , Pseudomonas aeruginosa , Klebsiella pneumoniae , and Acinetobacter baumannii . Similarly, functionalized Au NPs have also been observed to be effective against both Gram-negative and Gram-positive uropathogens, including multidrug-resistant pathogens .…”
Section: Inhibitory Action Of Nanoparticles Against Microbesmentioning
confidence: 99%
See 2 more Smart Citations